2009
DOI: 10.1530/eje-08-0924
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin levels are decreased in non-obese prepubertal children born large for gestational age

Abstract: Background: Ghrelin is the natural ligand of GH secretagogue receptor. It has several metabolic functions including regulation of food intake, energy homeostasis, and body weight. An inverse relationship between fasting plasma ghrelin and insulin concentrations has been shown. Being born large for gestational age (LGA) has an increased risk of developing insulin resistance. Objective: The aim of this study was to evaluate ghrelin levels in LGA born children who have no obesity at prepubertal ages and the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
1
3
0
1
Order By: Relevance
“…This sustained elevation of ghrelin might be needed for the compensatory growth which they are subjected, but it does not correlate to the degree of catch-up growth achieved nor with the levels of insulin found. Similar results were published the following year by Darendeliler et al [31] analyzing prepubertal children who were born large for gestational age, reporting that nonobese prepubertal youngsters had lower ghrelin levels compared to AGA born counterparts, proposing that birth weight is in fact a fundamental determinant in ghrelin levels during childhood. …”
Section: Nutrition Of the Fetus: Under Versus Oversupporting
confidence: 84%
“…This sustained elevation of ghrelin might be needed for the compensatory growth which they are subjected, but it does not correlate to the degree of catch-up growth achieved nor with the levels of insulin found. Similar results were published the following year by Darendeliler et al [31] analyzing prepubertal children who were born large for gestational age, reporting that nonobese prepubertal youngsters had lower ghrelin levels compared to AGA born counterparts, proposing that birth weight is in fact a fundamental determinant in ghrelin levels during childhood. …”
Section: Nutrition Of the Fetus: Under Versus Oversupporting
confidence: 84%
“…The present results are also in accordance with previous studies of young children which showed that infants who were born with a low birth weight ( 13 ) or born preterm ( 13 , 28 , 29 ) had elevated levels of fasting PYY, reflecting greater satiety. The results from previous studies in which the association between birth weight and fasting levels of ghrelin has been investigated are conflicting, showing no differences ( 14 , 16 ) , decreased ( 13 ) or even elevated ( 15 , 17 ) ghrelin levels among children born with a low birth weight compared with controls. To our knowledge, only one study has investigated the effect of birth weight on postprandial appetite regulatory hormone responses in adulthood, and detected no effect of birth weight ( 22 ) .…”
Section: Discussionmentioning
confidence: 94%
“…Six articles met the criteria for meta-analysis (19,20,(23)(24)(25)(26). The excluded articles from the study (n=23) included the following: 5 articles presented the effect of breast milk ghrelin on growth in infants (6,18,21,22,27), 8 articles expressed no correlation between infants' serum ghrelin and growth (2, 17, 28-33), 3 articles were of descriptive nature (34-36), and 6 articles had an intervention group (37)(38)(39)(40)(41)(42).…”
Section: Resultsmentioning
confidence: 99%